Hubungan Kebiasaan Olahraga, Rasio Lingkar Pinggang Pinggul, dan Kebiasaan Merokok dengan Kadar Kolesterol Total Pasien Poliklinik Jantung: The Relationship of Sports Habits, Circumference Waist Hip Ratio, and Smoking Habits with Total Cholesterol Levels Heart Policlinic Patients - Reni Purnama Indah Lestari; Harna; Anugrah Novianti (Svasta Harena: Jurnal Ilmiah Gizi, 2020)
High cholesterol levels constitute 56% of the factors that contribute greatly to the cause of CHD. Coronary heart disease (CHD) is a disease of the heart and blood vessels caused by narrowing of the coronary arteries. The purpose of this study to analyze the relationship of sports habits, circumference waist hip ratio, consumption pattern, level of fiber adequacy, and smoking habits with total cholesterol levels heart policlinic patients RSUD Banten. This type of research uses a cross sectional design, with a sample of 96 respondents namely heart policlinic patients. Analysis of the data used in this study is the Chi-square test. The Results show Respondents with normal nutritional status were 66.70%, respondents who consumed cholesterol-lowering drugs were 55.2%. Respondents with normal cholesterol levels were 53.10%, respondents with exercise habits were 56.25%, respondents with RLPP were at a risk of 71.87%. Respondents did not smoke as much as 66.70%. There was a relationship between exercise habits, hip waist circumference ratio, to total cholesterol levels (p <0.05). There is no relationship between smoking habits on total cholesterol levels (p> 0.05). This study concluded that the sports habits, RLPP, affect total cholesterol levels, while smoking does not affect total cholesterol levels.